Influenza and respiratory syncytial viruses: Efficacy of different diagnostic assays - Rahman, MM; Wong, KK; Alfizah, H; Hussin, S; Isahak, I (Professional Medical Publications, 2024)
Objective: To determine the efficacy of cell culture, immunoflourescence Assay (IFA) and real time polymerase chain reaction (rRT-PCR) in relation to diagnosis of influenza and Respiratory Syncytial Virus (RSV). Methods: Total 2781 specimens of throat swabs and nasopharyngeal aspirates were obtained from patients suspected of respiratory viruses' infections from January 2009 to December 2011 at Universiti Kebangsaan Malaysia Medical Centre(UKMMC). The specimens were processed by cell culture and immunoflurescence assay (FA) and (rRT-PCR). Results: Thirty three (1.19%) specimens were positive for influenza virus A and 42 (1.51%) were positive for RSV by cell culture and IFA. On the other hand, rRT-PCR was able to identify 189 of 505 (37.43%) specimens in which 65 were influenza A virus and 124 were RSV. Sensitivity of rRT-PCR was 100% for both influenza A virus and RSV and specificity was 88% and 77% for influenza A virus and RSV, respectively. Conclusion: rRT-PCR diagnosed respiratory viruses in shorter time with a high level of sensitivity in comparison to conventional assays - cell culture and IFA. These advantages help in managing patients by saving cost and hospitalization stay.